Prevalence of Late-Onset Multiple Sclerosis in Fars Province, Southern Iran: - Sharifian, Maryam; Izadi, Sadegh; Nikseresht, Alireza; Rafiee, Shima (Galen Medical Journal, 2014)
Background: Multiple Sclerosis (MS) is the most common demyelinating and inflammatory disease of the central nevus system especially in young adults, but in a subgroup of patients the first clinical symptoms present after the age of 50. This clinical presentation is defined as Late-Onset Multiple Sclerosis (LOMS). The incidence and prevalence of MS including LOMS vary geographically. The aim of this study is to determine epidemiological characteristics of LOMS in Fars province, South of Iran.Materials and Methods: All patients aged over 50, known to have had definite MS according to MC Donald’s criteria, being members of Shiraz University Multiple Sclerosis Database (SUMSD), were evaluated in this study. The following data were recorded via a questionnaire indicating gender, age at the time of diagnosis, clinical course and details of disease- modifying therapies (Beta-Interferon).Results: Among a total of 1705 patients, 7.2% were identified as having LOMS and 3.1% identified as having very late-onset MS (VLOMS). Mean age of the patients with LOMS at the time of diagnosis was 58.81 ± 2.6 years (20.8% were male and 107 (79.2%) were female). 8.9 % had EDSS 6 and more. 89.1% of patients received Beta-Interferon as a disease-modifying treatment including Avonex (16.3 %), Cinovex (32.6%), Rebif (14.1%) and Betaferon (26.1 %). Conclusion: In our study, 7.2% of all MS patients were identified as LOMS. In LOMS subgroup, clinical history and para-clinical data should be thoroughly evaluated to exclude more common conditions like cerebrovascular disease. [GMJ. 2014;3(4):228-31]